Accurate words: Mario Benedetti, between aphorism, greguería and haiku (Revista de Crítica Literaria Latinoamericana, 2013)
This article is an analysis of the brief forms cultivated by Mario Benedetti, present in "garguerías", included in Mejor es meneallo (1965), continued in "Graffiti without walls" of Despistes y franqueas (1992), "trifles" of Defensa propia (2004) and "trinkets" of Vivir adrede (2007), as well as in some of his discussed "haikus". Some essential features of Benedetti’s poetics will be delineated through the study of these texts, marked by aphorism, surprising images, depth of thought and their common inheritance from "greguería". Thus, I will comment on his use of irony and humor, his main rhetorical strategies and the reflection of fundamental topics such as political commitment, denunciation of the evils of our civilization, exile, consciousness of the passage of time, and, finally, attention paid to love, considered the best way to save ourselves in a world in crisis.
Keywords: Mario Benedetti; aphorism; "greguería"; haiku; humor